Pendampingan Kalibrasi Arah Kiblat sebagai Upaya Peningkatan Ketepatan Praktik Ibadah - Faizah, Isniyatin (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
This community service program aims to improve the accuracy of qibla determination in the mosques and prayer rooms of Tepanas Hamlet through a Community Based Research (CBR) approach. Initial observations revealed qibla deviations ranging from 1° to 15°, caused by the use of traditional methods without astronomical verification and the low level of falak literacy among worship place administrators. Through the CBR model, activities were designed participatorily through several stages: problem identification, planning, training, field action, evaluation, and empowerment. The training focused on the use of the Mizwala, a highly accurate sun-shadow-based instrument, complemented by verification using GPS applications. During the field action stage, five worship facilities were successfully recalibrated, resulting in the elimination of all deviations and full alignment with the theoretical azimuth. The evaluation indicated a significant improvement in participants’ technical competence, including the ability to read the Mizwala scale and validate measurement results. The program continued with the establishment of local falakiyah cadres as a sustainability measure. The outcomes demonstrate that the CBR approach is effective in enhancing community capacity while producing an accurate, participatory, and sustainable model for qibla calibration.